2022
DOI: 10.3390/genes13111986
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated Expression of Circular RNAs Is Associated with Immune Evasion and Leukemia Relapse after Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Background: Circular RNAs (circRNAs) are a novel class of epigenetic regulators that participate in leukemogenesis. However, their roles in leukemia relapse after transplantation remain unclear. Methods: We defined the circRNAs profile of the bone-marrow-enriched CD34+ cells from ten acute myeloid leukemia (AML) patients after transplantation (five relapse [RE] and five continuous complete remission [CR]) and four healthy controls (HCs) by RNA-seq. Differentially expressed circRNAs were validated using real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Various enucleated blood cells aggregate additional circRNAs [ 121 ]. It has been found that dysregulation of circRNAs could be involved in the mechanisms that pathogens use to avoid immune response linked with relapse of amyloid leukemia (AML) and relapse blasts [ 122 ]. It was found that patients who had a relapse in acute myeloid leukemia (AML) had a specific circRNA profile compared to patients who were healthy or in complete remission.…”
Section: Functions Of Circular Rnamentioning
confidence: 99%
“…Various enucleated blood cells aggregate additional circRNAs [ 121 ]. It has been found that dysregulation of circRNAs could be involved in the mechanisms that pathogens use to avoid immune response linked with relapse of amyloid leukemia (AML) and relapse blasts [ 122 ]. It was found that patients who had a relapse in acute myeloid leukemia (AML) had a specific circRNA profile compared to patients who were healthy or in complete remission.…”
Section: Functions Of Circular Rnamentioning
confidence: 99%
“…Specifically, lncRNAs NONHSAT040475, NONHSAT142151 and FR118417 were found to be strongly associated with the BCR signaling pathway in cGVHD pathogenesis ( 119 ). Another class of non-coding RNAs, termed circular RNAs, has been associated with increased relapse risk in AML patients ( 120 ).…”
Section: Epigenetic Regulation Of Hematopoietic Stem Cells Before And...mentioning
confidence: 99%
“…Most studies have focused on circRNAs encoded by the cells at various stages of their life, during which they play innumerable and fundamental roles [57], such as miRNA sponges [58], regulation of cellular proliferation [59], protein-binding [60], splicing regulation [61] and roles in the immune system [62]. Due to their involvement in all these crucial functions, it is assumed that cellular circRNAs could have strong correlation with various diseases.…”
Section: Functions Of Circrnasmentioning
confidence: 99%